The Pictor Technique: A Method for Exploring the Experience of Collaborative Working. (August 2013) - King, Nigel; Bravington, Alison; Brooks, Joanna; Hardy, Beth; Melvin, Jane; Wilde, David
Collaborative working is a crucial part of contemporary health and social care. Researching the experiences of those involved—as professionals, patients, or carers—is challenging, given the complexity of many cases and the taken-for-granted nature of roles and identities in relation to it. In this article we introduce the Pictor technique for exploring experiences of collaborative working. This is a visual technique in which participants construct a representation of roles and relationships in a particular case using arrow-shaped adhesive notes or cards. The chart so produced helps the participant tell the story of his or her experience and serves as a focus for further exploration with the researcher. We describe the background to Pictor and illustrate its use with professionals, patients, and carers, drawing on recent and current research. We examine how Pictor relates to other visual methods, and conclude by considering how the technique might be developed in the future.